Does disclosure deter or trigger litigation? - Field, Laura; Lowry, Michelle; Shu, Susan (Journal of Accounting and Economics, 2005)
Securities litigation poses large costs to firms. The risk of litigation is heightened when firms have unexpectedly large earnings disappointments. Previous literature presents mixed evidence on whether voluntary disclosure of the bad news prior to scheduled earnings announcements deters or triggers litigation. We show that the counterintuitive finding in prior literature that disclosure triggers litigation could be driven by the endogeneity between disclosure and litigation. Using a simultaneous equations methodology, we find no evidence that disclosure triggers litigation. In fact, consistent with economic arguments, our evidence suggests that disclosure potentially deters certain types of litigation.